Outbreak by Hypermucoviscous Klebsiella pneumoniae ST11 Isolates with Carbapenem Resistance in a Tertiary Hospital in China - Zhan, Lingling; Wang, Shanshan; Guo, Yinjuan; Jin, Ye; Duan, Jingjing; Hao, Zhihao; Lv, Jingnan; Qi, Xiuqin; Hu, Longhua; Chen, Liang; Kreiswirth, Barry N.; Zhang, Rong; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Hypervirulent and multidrug resistant Klebsiella pneumoniae strains pose a significant threat to the public health. In the present study, 21 carbapenem-resistant K. pneumoniae isolates (CRKP) were determined by the string test as hypermucoviscous K. pneumoniae (HMKP), with the prevalence of 15.0% (21/140) among CRKP, and 1.1% (21/1838) among all K. pneumoniae isolates. Among them, 7 (33.3%) and 1 (4.76%) isolate belonged to capsular serotype K20 and K2 respectively, while 13 (61.9%, 13/21) weren’t successfully typed by capsular serotyping. All the 21 isolates were carbapenemase-producers and were positive for blaKPC-2. In addition to blaKPC-2, all the 21 isolates except one harbor blaSHV-11, and 15 carry extended-spectrum β-lactamase gene blaCTX-M-65. The virulence-associated genes with more than 90% of positive rates among 21 isolates included ureA (100%, 21/21), wabG (100%, 21/21), fimH (95.2%, 20/21), entB (95.2%, 20/21), ycf (95.2%, 20/21), ybtS (95.2%, 20/21) and iutA (90.5%, 19/21). rmpA and aerobactin were found in 57.1% (12/21) isolates. Five sequence types (STs) were identified by multilocus sequence typing (MLST), including ST11 (11 K-non capsule typable and 5 K20 isolates), ST268 (1 K20 isolate and 1 K-non capsule typable isolate), ST65 (1 K2 isolate), ST692 (1 K-non capsule typable isolate) and ST595, a novel sequence type (1 K-non capsule typable isolate). Pulsed-field gel electrophoresis (PFGE) results showed two major PFGE clusters, of which cluster A accounts for 6 ST11 isolates (28.6%) and cluster B includes 8 ST11 isolates (38.1%, 8/21). Ten and six ST11 isolates were isolated from 2014 and 2015, respectively, while 8 were isolated from the same month of December in 2014. Ten isolates were collected from the intensive care unit (ICU), and all except one belonged to ST11. Additional 4 ST11 isolates were collected from patients in non-ICU wards, who had more than 10 days of ICU stay history in 2014 prior to transfer to their current wards where the isolates were recovered. Taken together, the present study showed a hospital outbreak and dissemination of ST11 HMKP with carbapenem resistance caused by KPC-2. Effective surveillance and strict infection control strategies should be implemented to prevent outbreak by HMKP with carbapenem resistance in hospitals.